The Effectiveness of Emotion-Focused Couple Therapy on Marital Burnout in Couples with Experience of Emotional Divorce - Asghariganji, Askari (Applied Family Therapy Journal (AFTJ), 2026)
Objective: Emotional divorce is one of the common yet concealed phenomena in marital relationships and is associated with extensive psychological consequences, including marital burnout. The present study aimed to examine the effectiveness of Emotion-Focused Couple Therapy (EFCT) on marital burnout among couples with experience of emotional divorce.Methodology: The present research employed a quasi-experimental design with pretest, posttest, and follow-up phases including a control group. The statistical population consisted of all couples who referred to the Ganj-e Mehr Counseling Center in Babol in 2024. Using convenience sampling, 30 couples were selected and randomly assigned to an experimental group and a control group. Emotion-Focused Couple Therapy sessions were conducted once weekly in two-hour sessions over a period of 10 weeks. Marital burnout was measured using the Pines Marital Burnout Questionnaire. Data were analyzed using univariate analysis of covariance (ANCOVA) and multivariate analysis of covariance (MANCOVA).Findings: The results indicated a statistically significant difference between the experimental and control groups after the intervention. Emotion-Focused Couple Therapy significantly reduced marital burnout and its components among couples with experience of emotional divorce. Moreover, these effects remained statistically stable during the follow-up period (p < .001).Conclusion: Based on the findings, Emotion-Focused Couple Therapy can be considered an effective intervention for reducing marital burnout among couples, particularly those experiencing emotional divorce and who are at risk of formal separation.